Satellite nucleoli in the megakaryocytic lineage of rats - Janoutová, J; Likovský, Z; Smetana, K (Physiological research, 2001)
The present study was undertaken to provide more information on the incidence of satellite nucleoli in developmental stages of the megakaryocytic lineage. Satellite nucleoli representing solitary silver stained nucleolus organizer regions (AgNORs) present in nuclei in addition to other nucleolar types were observed in all stages of megakaryocytic development. However, the incidence of satellite nucleoli was more frequent in mature megakaryocytes than in less differentiated immature megakaryoblasts and naked megakaryocytic nuclei representing the terminal stages of megakaryocytic development after loss of the cytoplasm transformed to thrombocytes. There is a possibility that the increased incidence of satellite nucleoli in mature megakaryocytes might be due to the loss of AgNORs from active nucleoli characteristic for immature cells. The decreased incidence of satellite nucleoli in naked megakaryocytic nuclei might reflect their disintegration in the terminal stages of the megakaryocytic development.
Keywords: Cell Nucleolus; Male; Rats, Wistar; Megakaryocytes; Animals; potkani Wistar; Hematopoiesis; hematopoéza; mužské pohlaví; krysa rodu Rattus; megakaryocyty; organizátor jadérka; Rats; trombocyty; barvení stříbrem; zvířata; buněčné jadérko; Blood Platelets; Nucleolus Organizer Region; Silver Staining